PERSEPSI MASYARAKAT TENTANG IMUNISASI DI WILAYAH KERJA PUSKESMAS PAGAMBIRAN TAHUN 2017 - Nina Fitri (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Immunization is one of the prevention method that have been approved as an effort toeradicate and reduce severe infectious diseases.The achievement target of UCI in Padang was97%, but Pengambiran Health Care still have not reached the target, this meansnot all infant andchild gets full immunization andthis not only increases the individuals risk of diseases but alsoincreases the risk for the whole community.The design of this study was qualitative withphenomenological approach, conducted in the region of Pengambiran Health Care from January-March 2017. The selection of the informant was done by snowball sampling, total informan were15 people consisting of mothers and fathers who have a baby/toddler, Head of RT, Head of PKK,Staf of Posyandu, community leaders, and the Head of the Immunization Program in Health Care.Data collection was using indepth interviews. Data validation was done by triangulation. Theresults of the study brings out five: public understanding of immunization in babies and toddlers,social approach to community leaders, KIE done to the community about immunization, negativeissues about immunization in community such as fake vaccine, and the reasons parents did notbrought her child to immunization were.Recommendations in this study, need to improve thecommunity’s understanding of immunization throug effective communication of officials with thecommunity, prepare budget to hold meetings with community key figures so it can clear out thewrong understanding about immunization, intensify the KIE by health worker to all community,giving brochure and involve colleger practice to provide immunization information to the public.Keywords: Immunization, vaccines, KIE, health care, community